Measuring Emission Lines with JWST MegaScience Medium Bands: A New Window into Dust and Star Formation at Cosmic Noon - Brian Lorenz; Katherine A. Suess; Mariska Kriek; Sedona H. Price; Joel Leja; Erica Nelson; Hakim Atek; Rachel Bezanson; Gabriel Brammer; Sam E. Cutler; Pratika Dayal; Anna de Graaff; et al. (The Astrophysical Journal Letters, 2025)
We demonstrate the power of JWST-NIRCam medium-band photometry to measure emission line fluxes and study the dust and star formation properties of galaxies at cosmic noon. In this work, we present photometric emission line measurements and spatially resolved maps of H α and Pa β for 14 galaxies at 1.3 ≤ z ≤ 2.4, observed by the MegaScience medium-band survey and the UNCOVER spectroscopic survey. We measure line fluxes directly from medium-band photometry and compare with spectroscopic measurements from UNCOVER. We find reasonable agreement between the photometric and spectroscopic emission line fluxes for both H α and Pa β , with scatter <0.15 dex down to emission line equivalent widths of 10 Å. We also make a nebular dust measurement from the ratio Pa β /H α , finding an average nebular attenuation in the V band, A _V , of 1.4 with a standard deviation of 0.8. Our photometric A _V measurements show a slightly larger scatter of 0.5 mag when compared to spectroscopic measurements; however, this scatter may be partially caused by aperture effects. Finally, we produce spatially resolved maps of H α emission, Pa β emission, and the stellar continuum. We find offsets between H α and Pa β emission, especially for galaxies with high A _V , indicating dusty substructures. Furthermore, the correlation between H α and continuum emission decreases with increasing A _V , suggesting that the dustiest objects have clumpy dust and star formation distributions. Our study demonstrates the power of medium-band photometry to directly probe emission line strengths, star formation, and dust attenuation for hundreds of galaxies in UNCOVER and thousands of galaxies in upcoming JWST medium-band surveys.